MAP-2 as an early marker of hippocampal damage after perinatal asphyxia and neuroprotective properties of Palmitoylethanolamide - Capani, Francisco (2021)
Statement of the Problem: Diminish in the oxygen levels prompted short and long-term alterations insynapses and related structures that are related to neuronal dysfunction and death. Perinatal asphyxia (PA) isan obstetric complication produced by an impaired gas exchange that lead to neonatal mortality and is adeterminant factor for neurodevelopmental disorders (1,2). Cumulative experimental evidence refersPalmitoylethanolamide (PEA) exerts neuroprotective actions in different models of brain injury andneurodegeneration (3) . Accordingly, we have observed PEA treatment could ameliorate hippocampal deficitin microtubule associated protein-2 (MAP-2) 1 month after PA. Therefore, the aim of the present study was toassess earlier neuroprotective effects of this endogenous compound using correlative light and electronmicroscopy.Methodology & Theoretical Orientation PA was induced by placing newborn Sprague Dawley rats in a 37° C water bath for 19 minutes. PEA treatment (10 mg/kg) was administered subcutaneously during the firsthour of life. Hippocampal modifications were analyzed by Immunohistochemistry and electron microscopy atpostnatal day 21 (P21), once the animals had completed synapse formation and reflex maturation. In CA1region, a decrease in MAP-2 reactive area was observed at P21 as a consequence of PA. In this way, MAP-2appears as an early biomarker of PA-induced hippocampal damage (Fig 1). In addition, subcelularmodifications were observed using electron microscopy techniques. After PA, neuronal cell body showed clearsigns such as nuclear fragmentation, dark cytoplasm and vesicles accumulation. PEA reverted thesemodifications.Conclusion & Significance Therefore, PEA treatment could attenuate this hippocampal dendritic dysfunction,representing a putative neuroprotective agent for the developing injured brain. Future studies on long-termMAP-2 modifications might help determine the efficacy of PEA treatment on PA-induced dendriticcytoskeletal derangements.